Valuing quality seeds and species diversity in FLR: Simulation modelling for cost-benefit analysis - Roscioli, Federico; Thomas, Evert; Kozicka, Marta; Gotor, Elisabetta; Kettle, Christopher J. (2020)
Forest Landscape Restoration (FLR) aims at reestablishing the ecological functionality of degraded terrestrial ecosystems, as well as changing land-management practices to sustain local economic growth for the benefit of local livelihoods and for society in the long term. FLR projects embracing quality planting material, in terms of genetic diversity and site adaptation, provide better performances regarding growth and resilience. Consequently, they are expected to deliver a more efficient cost-benefit ratio. We propose a numerical model that simulates a one-hectare FLR project in order to explore the dynamics of the cost-benefit ratio over the period of 20 years. The model quantifies the impact of the use of quality planting material on the health of the plantation and its consequent economic value. A case study of a Prosopis pallida plantation in the dry forest of the north of Peru shows no relevant additional costs, but significant additional benefits of the use of quality planting material. This result holds both for an intensive commercial plantation and a conservation project that entails almost zero maintenance.